ANALISIS KAUSALITAS BENCANA TANAH LONGSOR DI KABUPATEN PURWOREJO MENGGUNAKAN METODE PROBLEM TREE ANALYSIS - Setyoko, Alfi; Satria, Ananda Zahra; Syaiful, Muhammad; Prasetya, Rizal Marefa Ardian (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2026)
ANALYSIS OF PROBLEM TREES IN LANDSLIDE DISASTERS IN PURWOREJO DISTRICT, CENTRAL JAVA PROVINCE Landslides in Purworejo Regency are a recurring geological phenomenon caused by the region’s morphological characteristics, which are dominated by hilly and mountainous terrain combined with high rainfall. This study aims to identify the cause–effect relationships between the contributing factors and the impacts of landslides using the Problem Tree Analysis method. The method was applied by utilizing various secondary data sources, including journals, books, reports, and online materials, to map the root causes, core problems, and resulting impacts. The analysis shows that the primary causes of landslides are a combination of hilly and mountainous landforms, unstable slopes, high rainfall intensity, sandy–clay soil textures, and human activities involving land-use changes that do not align with land capability. The resulting impacts include infrastructure damage, soil quality degradation, psychological effects on the community, economic losses, and casualties. The problem tree analysis provides a causal overview of the landslide issues and serves as a foundation for developing mitigation strategies based on an understanding of the underlying causes. The findings are expected to serve as a practical reference for local governments and stakeholders in improving disaster risk reduction efforts in Purworejo Regency.